What do we really know about how velvet worms mate? - Monge-Nájera, Julián (2019)
After more than a century of studying a phylum that has over 200 species, we only have three reports of the mating itself. Insemination can occur vaginally or through the skin, and it is suspected that the male simply places its genital opening against the vulva and inserts the spermatophore. However, in the particular case of a few Australian onychophorans, males insert it with a specialized head structure, and the spermatophore also serves as a vaginal plug, preventing insemination by other males.